Common Pronunciation Mistakes in Non-native Speakers: A Review - Rakaisa Langit Bengras Somara; Afief Fakhruddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2021)
Pronunciation is one of language micro-skill that should be mastered in order to create a clear and effective communication. This article aims to provide a brief review of some common mistakes in pronunciation at various L2 speakers by focusing into researches on related topic. By noticing the problem that occurred, English teachers may develop a better plan for future to avoid the same mistakes. The similarity between non-native learners, such as Chinese, Indonesian, Palestinian, Turkish and Vietnamese, is they tend to make mistakes in sound that do not exist in their first language.